Knee Surgery - Reconstruction and Replacement 2020
DOI: 10.5772/intechopen.89565
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness after Primary Total Knee Arthroplasty

Abstract: Total knee arthroplasty remains the definitive treatment for end-stage osteoarthritis of the knee. Despite being a very successful intervention in terms of relieving pain and returning a patient's function, it is not without complications. Post-operative stiffness after total knee arthroplasty is one of those complications that can be puzzling for physicians and debilitating for patients. While the etiology of stiffness is multifactorial, the treatment options are essentially limited to manipulation under anes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…For the COVID-19 group, any shortness of breath, chest pain, or blood-streaked sputum suggestive of pulmonary embolism were evaluated using a pulmonary thromboembolism CT [ 23 ]. Stiffness was defined by using a cut-off of approximately 95° of flexion that prevented the patient from performing most of the activity [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…For the COVID-19 group, any shortness of breath, chest pain, or blood-streaked sputum suggestive of pulmonary embolism were evaluated using a pulmonary thromboembolism CT [ 23 ]. Stiffness was defined by using a cut-off of approximately 95° of flexion that prevented the patient from performing most of the activity [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have reported stiffness and persistent pain following TKA. Around 4-16% of patients experience stiffness after total knee arthroplasty (Singh et al, 2019). Risk factor of post-knee arthroplasty stiffness are divided into three categories, which are: preoperative, intraoperative, and postoperative factors (See Table 1).…”
Section: Introductionmentioning
confidence: 99%